PWE-101 Post-Investigation Colorectal Cancer Rates at Imperial College Healthcare NHS Trust London, Exploring New Calculation Methodology. (17th August 2016) - Woodfield, G; Carasco, C; Foster, M; Smith, G
Abstract : Introduction: Post colonoscopy colorectal cancer (PCCRC) rates have been proposed as a key quality indicator of a colonoscopy service. Rates vary according to the calculation methodology used. 1 A recent study used the number of colonoscopies done within 3 years of a colorectal (CR) cancer diagnosis as the denominator for PCCRC calculations, rather than the total number of cancers. This gave higher PCCRCs that previously calculated; 8.6% between 2001–2007 in the English NHS. 1 This study aims to calculate the PCCRC and post- CT virtual colonoscopy CR cancer rate at Imperial College London. This is important in order to assess local practice, but also to explore methodology for calculating PCCRC rates, which is currently not standardised. Methods: All patients diagnosed with CR cancer between October 2014–2015 were identified using the Somerset cancer database for Imperial College Trust. All colonoscopy and CT virtual colonoscopy results in the 3 years preceding the diagnostic investigation were reviewed. GPs were contacted, to detect any investigations done outwith Imperial Trust (23 responded). Where patients had multiple surveillance colonoscopies, only the latest could be counted as false negative, as in previous studies. 1 Results: 272 patients were initially identified. 99 were excluded due to lack of data, duplications, non-CR cancer diagnoses including anal cancer or tumour recurrences. 173 patients were included for analysis. 103 had been diagnosed by colonoscopy, 70 by CT. In this cohort 115 colonoscopies and 72 CT virtual colonoscopy scans were performed (or CT abdomen if this was the diagnostic test). Of 115 colonoscopies, 28 were done within the Bowel Cancer Screening Programme (BCSP), 75 were done for symptoms, 12 were done for surveillance. There were no false negative colonoscopies in the BCSP group. In the symptomatic group there were 3, and in the surveillance group there were 2 false negative colonoscopies. The overall PCCRC was 4.3%. Of the 72 CT scans, there were 2 false negative scans, The post CTVC CR cancer rate was 2.8%. Conclusion: Our PCCRC rate of 4.3% over one year compared favourably to the estimated National PCCRC rate of 7.3% in 2007 (8.6% between 2001–2007) using the same methodology for calculations. 1 Imperial NHS Trust is performing in line with predictions of improved colonoscopy pick-up rates over time. 1 This study adds to literature regarding methodology for calculating PCCRC rate, and suggests that it be further refined to provide a clear calculation standard. Reference: 1 Morris EJA, Rutter MD, Finan PJ, et al . Post- colonoscopy colorectal cancer (PCCRC) rates vary considerably depending on the method used to calculate them: a retrospective observational population-based study of PCCRC in the English National Health Service. Gut 2015;64 :1248-1256 Disclosure of Interest: None Declared